Impacts of the U.S.-China Trade War on Lithium-ion Battery Supply Chains: A Network Analysis Approach - Yang, Yuanhao (International Journal of Global Economics and Management, 2024)
Lithium is a critical strategic resource essential for electric vehicles and lithium-ion batteries, both of which play pivotal roles in the transition to renewable energy. This study examines the global lithium supply chain, analyzing four representative products—lithium carbonate, lithium hydroxide, lithium-ion batteries, and electric vehicles—across the upstream, midstream, and downstream sectors from 2012 to 2023. Utilizing complex network theory, the research explores the structural characteristics and dynamic evolution of global trade networks before and after the U.S.-China trade war. The findings reveal that the lithium supply chain exhibits strong small-world characteristics, with high clustering coefficients and relatively short path lengths across all stages. Differences in trade network patterns were observed between products: lithium hydroxide shows more regional concentration, while electric vehicles demonstrate a more globalized trade network. These insights offer important implications for understanding supply chain resilience and vulnerability in the face of geopolitical conflict.